Unsupported MoS2-Based Catalysts for Bio-Oil Hydrodeoxygenation: Recent Advances and Future Perspectives - Cao, Jing; Zhang, Youming; Wang, Li; Zhang, Cen; Zhou, Congshan (Frontiers in Chemistry, 2022)
In recent years, unsupported MoS2-based catalysts have been reported as promising candidates in the hydrodeoxygenation (HDO) of bio-oil. However, preparing MoS2-based catalysts with both high activity and good stability for HDO reaction is still challenging and of great importance. Hence, this mini-review is focused on the recent development of unsupported MoS2-based HDO catalysts from the understanding of catalyst design. The three aspects including morphology and defect engineering, metal doping, and deactivation mechanism are highlighted in adjusting the HDO performance of MoS2-based catalysts. Finally, the key challenges and future perspectives about how to design efficient catalysts are also summarized in the conclusions.